Skill hub: a conceptual business model that gives job opportunities for freelancers and B40 community - Amran, Muhammad Ammar Zakwan; Khairul Akmal, Siti Nur Adawiyah; Sapee-e, Nuridah; Ahmad Dahlan, Abdul Rahman (Kulliyyah of Information and Communication Technology International Islamic University Malaysia, 2022)
The goal of this paper is to present a conceptual Skill Hub business model, complete with its digital platform and apps, that is in line with the United Nations Sustainable Development Goals (SDG). The Skill Hub business concept and platform offer potential advantages to its consumers. The Customer Segments in this study are the people who are busy and need an immediate service, the service providers who do not have a good platform to promote their services, the low-income people (B40) who lack the contemporary skill set, and the donors who do not have the trusted platform to donate their money. Skill Hub offers quick services in many fields without the need to waste time in searching, surveying and giving solutions to the unemployment issues. The Sustainable Development Goals (SDG) that can be found in this paper are SDG 1 - No Poverty (the issues of poverty in Malaysia), SDG 8 - Decent Work and Economic Growth (concerns with unemployment and underemployment problems), and SDG 12 - Responsible Consumption and Production (training that ensuring long-term consumption). The Design Thinking (DT) methodology is used in this study to identify significant challenges and propose possible effective solutions. This process entails completing a literature research, benchmarking, and surveys or interviews to understand and define the issue space of consumer segments, as well as brainstorming, prototyping, and testing potential solutions. The business modelling tools that have been used for the problem and solution area of the customers are Environmental Map (EM), Business Model Canvas (BMC), Value Proposition Design Canvas (VPC) and Strategy Canvas (SC). The initial business model prototype was prepared by EM, BMC and VPC while the low-fidelity Skill Hub prototype was created and tested with various consumer segments. Thus, the Skill Hub business concept and platform offer potential advantages to its consumers and come out with the solution for their difficulties and pains.